(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Within the last 30 years Additive Manufacturing (AM) became an important method for the treatment of craniofacial injuries. This is true for the direct application of AM made implants as well as for its indirect application via counter casting. Many successful cases have been published. But little is known about the long term behavior, especially if applied on big heavy loaded implants and older people. The report is a 10 years study about a 64 years old planter that suffered from a severe head injury. After several treatments he finally got an AM implant made from Titanium and recovered successfully.